Memory Disorders and the Extension of the Postmodern Fictional Boundary. Paul Auster’s Man in the Dark - Saliba-Salman, Hana (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2019)
The genre of memory disorder fiction makes visible a correlation between the condition of postmodernity and memory disorders, as they enmesh the subject in a conspiracy concerning the past. In Man in the Dark (2008), Paul Auster uses insomnia and amnesia as narrative mechanisms to reflect upon the 9/11 attacks. This invocation of memory disorders bring forward new insights about personal and collective traumatic memories and demonstrates the role of fiction to transcend reality.